Expression of antimicrobial peptide genes oscillates along day/night rhythm protecting mice skin from bacteria. Issue 10 (17th November 2020) - Bilska, Bernadetta; Zegar, Aneta; Slominski, Andrzej T.; Kleszczyński, Konrad; Cichy, Joanna; Pyza, Elzbieta
Abstract: Antimicrobial peptides (AMPs) are important components of the innate immune system and are involved in skin protection against environmental insults and in wound healing. Herein, we assessed the gene expression of chemerin ( Rarres2 ), cathelicidin CRAMP ( Camp ), and three β ‐defensins ( Defb1, Defb3, and Defb14 ) in mouse skin during light/dark cycle (LD 12:12) and constant darkness (DD). Next, we examined the survival of bacteria applied on the skin at specific times during the day. We found that the expression of Rarres2, Camp, and Defb1 was the highest at 4 h after the beginning of darkness, during high activity of mice. These rhythms, however, were not maintained under DD in the skin but were present in the liver. This indicated that in the case of skin, a circadian input was masked by daily changes of light in the environment. In contrast, Defb3 and Defb14 showed the highest mRNA levels when the mice slept, and these rhythmic mRNA oscillations were maintained under DD. This shows that Rarres2, Camp, and Defb1 levels in the skin are correlated with high locomotor activity in mice and they are controlled by daily changes of light and dark. Alternatively, oscillations in the mRNA levels of Defb3 and Defb14 seem to protect skin and heal wounds during sleep. These rhythms are maintained under DD, indicating that they are regulated by a circadian clock. Our study suggests that daily AMP expression affects the survival of bacteria on the surface of skin, which depends on the phase of AMP cycling.